Evolution of selenophosphate synthetases: emergence and relocation of function through independent duplications and recurrent subfunctionalization - Mariotti, Marco; Santesmasses, Didac; Capella-Gutierrez, Salvador; Mateo, Andrea; Arnan, Carme; Johnson, Rory; D'Aniello, Salvatore; Yim, Sun Hee; Gladyshev, Vadim N.; Serras, Florenci; Corominas, Montserrat; Gabaldón, Toni; et al. (Genome Research, 2015)
Selenoproteins are proteins that incorporate selenocysteine (Sec), a nonstandard amino acid encoded by UGA, normally a stop codon. Sec synthesis requires the enzyme Selenophosphate synthetase (SPS or SelD), conserved in all prokaryotic and eukaryotic genomes encoding selenoproteins. Here, we study the evolutionary history of SPS genes, providing a map of selenoprotein function spanning the whole tree of life. SPS is itself a selenoprotein in many species, although functionally equivalent homologs that replace the Sec site with cysteine (Cys) are common. Many metazoans, however, possess SPS genes with substitutions other than Sec or Cys (collectively referred to as SPS1). Using complementation assays in fly mutants, we show that these genes share a common function, which appears to be distinct from the synthesis of selenophosphate carried out by the Sec- and Cys- SPS genes (termed SPS2), and unrelated to Sec synthesis. We show here that SPS1 genes originated through a number of independent gene duplications from an ancestral metazoan selenoprotein SPS2 gene that most likely already carried the SPS1 function. Thus, in SPS genes, parallel duplications and subsequent convergent subfunctionalization have resulted in the segregation to different loci of functions initially carried by a single gene. This evolutionary history constitutes a remarkable example of emergence and evolution of gene function, which we have been able to trace thanks to the singular features of SPS genes, wherein the amino acid at a single site determines unequivocally protein function and is intertwined to the evolutionary fate of the entire selenoproteome.